2021
DOI: 10.3390/met11010138
|View full text |Cite
|
Sign up to set email alerts
|

Flow Stress Behaviour and Static Recrystallization Characteristics of Hot Deformed Austenite in Microalloyed Medium-Carbon Bainitic Steels

Abstract: In the past decade, efforts have been focused on developing very fine, medium-carbon bainitic steels via the low-temperature (typically 300–400 °C) ausforming process, which not only enables shorter isothermal holding times for bainitic transformation at low temperatures, but also offers significantly improved strength. This paper describes static recrystallization (SRX) characteristics of austenite in four medium-carbon 2%Mn-1.3%Si-0.7%Cr steels with and without microalloying intended for the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The strain exponent of − 2.5 was also used by Hodgson and Gibbs [46] for C-Mn, Ti-, and V-steels. Moreover, the values of p in the current study are comparable with those reported by Kaikkonen et al [2] for microalloyed medium carbon bainitic steels which range from − 1.7 to − 2.7.…”
Section: Estimation Of the Power Of Strain (P)supporting
confidence: 91%
See 3 more Smart Citations
“…The strain exponent of − 2.5 was also used by Hodgson and Gibbs [46] for C-Mn, Ti-, and V-steels. Moreover, the values of p in the current study are comparable with those reported by Kaikkonen et al [2] for microalloyed medium carbon bainitic steels which range from − 1.7 to − 2.7.…”
Section: Estimation Of the Power Of Strain (P)supporting
confidence: 91%
“…5a show work hardening and dynamic recovery prior to stress relaxation at all deformation temperature. Thus, the static restoration (recovery and recrystallization) process can be characterized using the relaxation after hot compression [2]. The flow stress of the examined steels is, as predicted, highly influenced by the deformation temperature.…”
Section: Flow Stress and Relaxation Behaviormentioning
confidence: 92%
See 2 more Smart Citations
“…Due to the combination of high strength and toughness, high-grade pipeline steels, such as, X70, X80, and X100, has been extensively studied [ 1 , 2 , 3 , 4 , 5 ]. Thermo-mechanical control process (TMCP) is an indispensable and important technology in the manufacture of high-grade pipeline steels, which mainly involves the thermal deformation process of steel plates.…”
Section: Introductionmentioning
confidence: 99%